(untitled) (Proceedings of International Conference on Special Education, 2019)
Education is one of the facilities for mankind to develop itself, without exception for those who have limited or the specific needs. Hence inclusive education as a means of education to fulfill all children. Implementation inclusive education is done in several schools inclusive in various countries, including in indonesia. In indonesia has done the implementation inclusive, several education one of them is in jakarta regional. Jakarta is the areas that is visible significant implement inclusive education. Based on the above explanation so this report is written to get a how implementation inclusive education high at the school level. Used descriptive research qualitative study. Then instrument used is interview various sources, observation of facilities school and learning process, and documentation. The data that has been obtained and analyzed and been validated by triangulation triangluasi source of data and. The research found the implementation of inclusive education in schools ‘x ‘ Jakarta. Schools ‘x’ Jakarta is not completely implement school inclusive education inclusive. This is because there are some requirements of school education providers that have not been inclusive, namely: schools did not using the curriculum entirely flexible and there are a few flaws in means and education infrastructure in accordance with standard operating procedure.